Three Dimension Structure Modeling of The Superoxide Dismutase (SOD) of Rice (Oryza sativa) Using Fold Recognition Method Using Phyre2 Web Server - Noer Komari Komari (Program Studi Kimia, Universitas Lambung Mangkurat, 2022)
Determining the 3D structure of proteins using laboratory instrumentation is time-consuming and expensive. The in silico method can be used as an alternative to predict the 3D structure of proteins, such as the fold recognition method. This study aims to create a 3D structural model of rice's (Oryza sativa) protein superoxide dismutase (SOD). The 3D structure modeling of the protein was carried out with the Phyre2 web server. The protein sequence was obtained from the UniProt KB database with the code A0A6F8FUX1. The results showed that the suitable template used to build the model was the template with the code c1unfX. The c1unfX template has a coverage value of 80%, 100% confidence, and i.d. of 51%. Validation of the model with the PROCHECK program showed that the most favored area on the Ramachandran Plot was 87.8%, and the disallowed area was 1.1%. The disallowed area, which is still below 15%, indicates that the three-dimensional structure model of the SOD protein built from the c1unfX template has good a value.